2020
DOI: 10.21203/rs.2.17241/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Active and latent tuberculosis in refugees and asylum seekers: a systematic review and meta-analysis

Abstract: Background: In 2018, there were 70.8 million refugees, asylum seekers and persons displaced by wars and conflicts worldwide. Many of these individuals face a high risk for tuberculosis in their country of origin, which may be accentuated by adverse conditions endured during their journey. We summarised the prevalence of active and latent tuberculosis infection in refugees and asylum seekers through a systematic literature review and meta-analyses by country of origin and host continent. Methods: Articles publi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 15 publications
(18 reference statements)
0
11
0
Order By: Relevance
“…The quality of reporting of all included studies was evaluated by HLH and AC according to the CAse REport (CARE) guidelines 8 for case reports/series or the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) guidelines 9 for cross-sectional, case-control and cohort studies. A quality score 10 , 11 was calculated for each article based on a checklist of 36 items for CARE ( Supplementary Table S2 ) and 32-34 items for STROBE ( Supplementary Table S3 ), depending on the type of observational study. The presence of an item scored 1, absence scored 0 and the total was calculated.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The quality of reporting of all included studies was evaluated by HLH and AC according to the CAse REport (CARE) guidelines 8 for case reports/series or the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) guidelines 9 for cross-sectional, case-control and cohort studies. A quality score 10 , 11 was calculated for each article based on a checklist of 36 items for CARE ( Supplementary Table S2 ) and 32-34 items for STROBE ( Supplementary Table S3 ), depending on the type of observational study. The presence of an item scored 1, absence scored 0 and the total was calculated.…”
Section: Methodsmentioning
confidence: 99%
“…The presence of an item scored 1, absence scored 0 and the total was calculated. A percentage of the maximum possible score was also calculated and “high quality” was defined as any study achieving a score of 80% or greater 10 , 12 . “Low quality” was defined as any study with a score of < 80%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The total end year refugee population in Ethiopia was continuously increased from 491030 in 2014 to 728000 by 2017. The highest refugee population by 2017 were in Gambella refugee area (219,708), followed by Dollo Ado (197.952), Shire (109, 360), Asossa (55.726), Jijiga (35,024), Afar (15.390), and Mizan (11,761) [15].…”
Section: Study Settingsmentioning
confidence: 99%
“…Usually, majority (> 85%) of refugees originate from and remain within countries with high burdens of TB [10]. A recent systemic review and meta-analysis showed that TB prevalence in refugees and asylum seekers varied more according to countries of origin than the host country [11], whereas others reported association between continuous immigration (increase in migrant population) and increase in prevalence of PTB and EPTB [12], in TB case noti cation [13] and in case detection rate [14].…”
Section: Introductionmentioning
confidence: 99%